Exploring the Southwest - Gagne, Tammy (Exploring America's regions., 2018)
Examines the climate, history, famous natural and manmade landmarks, plant and animal life, industries, and peoples and cultures of the Southwest region of the United States. Includes primary sources, a facts section, critical thinking questions, color photographs and maps, a glossary, and online resources.